A model for the pyrolysis of two Nordic structural timbers. (3rd February 2021) - Rinta‐Paavola, Aleksi; Hostikka, Simo
SUMMARY: Performance‐based design of the timber structures' fire resistance is often based on the reduced cross section and thus relying on empirical and numerical assessment of the charring propagation. The current work aims to construct models for the pyrolysis of spruce and pinewoods to allow coupled simulations of the cross‐section reduction and burning rate in fire models. Kinetic models are formulated based on thermogravimetric data and supported by the heats of pyrolysis and combustion measurements by differential scanning calorimetry and microscale combustion calorimetry, respectively. The results from these small‐scale measurements are consistent with each other, and the heats of pyrolysis and combustion are determined for the wood primary components by fitting the simulations to the experimental results. Heat release models are constructed based on the small‐scale tests, and cone calorimeter experiments are used for the estimation of the physical properties and for the heat release model validation.